Bankruptcy Settlement: Causes and Consequences for Entrepreneurs According to Liquidators - Wakkee, Ingrid (Senate Hall, 2014)
This study addresses entrepreneurial bankruptcy settlement from an attitudinal perspective by exploring how liquidators perceive their interactions with entrepreneurs during bankruptcy settlement. We explore what personal attitudes influence the settlement process. A survey of 296 liquidators and 11 in-depth interviews show significant variances across liquidators in relation to empathy, learning orientation, cause attribution and stigmatisation of entrepreneurs. These factors appear to be important in the bankruptcy settlement process. Although no direct statistical effects on the extent to which liquidators involve entrepreneurs in the process were observed, and only limited effects on the duration of bankruptcy processes could be established, the interview data painted a balanced picture of how liquidators' attitudes and orientations affect their interaction with the entrepreneurs involved. A key finding was the notion that liquidators only have a limited insight into the actual negative consequence of a bankruptcy for the entrepreneur, particularly in their personal life. This seems to be caused partially by the fact that their empathy is typically directed at other stakeholders rather than at the entrepreneur involved. Also, we show how attribution plays a significant role in the bankruptcy settlement process. However, the effect of attribution is different than previously expected: it is not the liquidators' personal attribution of bankruptcy that influences if they are willing to involve an entrepreneur in the settlement process, but rather the liquidators' perception of the entrepreneur's attribution. Keywords: bankruptcy, liquidators, learning orientation, stigmatisation, empathy, entrepreneurs, mixed method research
Keywords: bankruptcy|liquidators|learning orientation|stigmatisation|empathy|entrepreneurs|mixed method research